Investigation of Chlorophyl-a Derived Compounds as Photosensitizer for Photodynamic Inactivation - Listiana Oktavia; Irma Mulyani; Veinardi Suendo (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Chlorophyll has unique physicochemical properties which makes them good as photosensitizer of Photodynamic Inactivation (PDI). The physicochemical properties of chlorophyll as photosensitizer can be optimized through several routes.  One of the possible route is by replacing the metal ion center of chlorophyll with other ions. In this research, the effect of coordinated metal ion in the natural chlorophyll-a was studied for bacterial growth (S. aureus) inhibition. The replacement of metal in the center of chlorophyll hopefully can improve the intensity of Intersystem Crossing Mechanism (ISC) lead to the formation of singlet oxygen species. The chlorophyll a and b were isolated from spinach via precipitation technique using 1,4 dioxane and water. The chlorophyll a and b were separated using sucrose column chromatography. The thin layer chromatography result showed that chlorophyll a (Rf: 0.57) had been well separated with chlorophyll b (Rf: 0.408). The absorption spectra of chlorophyll a and b showed that the Soret band was observed at 411 and 425 nm, while the Q band appeared at 663 and 659 nm. Replacement of metal ion center shifted the Soret band of chlorophyll- a derivatives to lower energy region, while Q-band was slightly shifted to the higher energy region. The absorption and the fluorescence intensity were  also observed decreasing after ion replacement. The Inhibition activity investigation over S. aureus showed the highest inhibition activity was exhibited by Zn-pheophytin-a (66.8%) followed by chlorophyll a (30.1 %) and Cu-pheophytin-a (0%). The inhibition activity is correlated with decreasing fluorescence intensity. The formation of singlet oxygen by ISC mechanism is hypothesized to deactivate the excitation state of Cu-pheophytin-a. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).